The Effect of Compensation on the Performance of Operational Employees at Gema Suara Adhitama Company, Central Jakarta - Harsono, Yhonanda; Maradona, Astuti (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2021)
The purpose of this study was conducted to determine whether there is an effect of compensation on employee performance in the Operations Section at PT. The echo of Adhitama Central Jakarta. The method used in this study is a descriptive method with a quantitative approach, sampling 65 respondents using a saturated sample, with analytical methods namely validity test, reliability test, simple linear regression analysis, correlation coefficient, coefficient of determination, and t test calculated using software SPSS version 24. Effect of Compensation on Employee Performance at PT. Gema Suara Adhitama Operational Section can be seen from the correlation coefficient obtained by 0.514, there is a fairly strong level of relationship between compensation and employee performance, then with a coefficient of determination obtained a figure of 0.264, which means that the influence of compensation has a contribution of influence on employee performance by 26.4%, while the remaining 73.6% is influenced by other factors not examined in this study. The resulting simple linear regression equation is Y = 24.489 + 0.386X, which means that if the value of X increases by one unit, the value of Y will increase by 0.386 with a constant of 24,484. The results of the partial significance test for the compensation variable (X) obtained tcount > ttable (4.751 > 1.998) with a significance value (0.000 < 0.05), then there is a positive and significant effect between the compensation variable (X) on employee performance (Y).